A Tailored, Bundle Care Intervention Strategy to Reduce Cardiac Mortality During the Hajj: A Population-Based, Before and After Study. (July 2019) - Al Faraidy, Khalid A.; Thalib, Lukman; Al Shammeri, Owayed; Bokhari, Fayez; Hersi, Ahmad; Alfaleh, Hussam; Kashour, Tarek
Background: Hajj is the largest human gathering with over 2 million people. We evaluated the effect of bundle care intervention on mortality. Methods: A population-based, before and after study compared the effect of an intervention on mortality. The intervention included recruitment of cardiac team, introducing 24/7 catheterization service, cardiac coordination, standardized cardiac care pathways, and establishment of an effective transportation system. Results: Cardiac mortality accounted for about 52% of all in-hospital deaths before intervention in 2009. This decreased significantly to 43.3%, 32.5%, and 19.7% in 2009, 2010, and 2011, respectively. In-hospital mortality of acute coronary syndromes was 4.7%, 4.6%, and 3.0%, in the years 2009, 2010, and 2011, respectively. Mortality due to other causes remained largely unaffected. There was no significant change in the national mortality due to cardiac causes over the same period provided a reassurance that the observed improvement in in-hospital acute coronary syndrome mortality was not due to overall improvement in health care. The numbers of cardiac catheterization procedures increased 3-fold and cardiac surgical procedures increased 5-fold between 2009 and 2011. Conclusions: In this study, we found that an evidence-based intensive bundle care intervention substantially reduced the cardiac mortality among the pilgrims assembling for Hajj in Makkah.